Antimony leaching from antimony-bearing ferric oxyhydroxides by filamentous fungi and biotransformation of ferric substrate - Urík, Martin; Polák, Filip; Bujdoš, Marek; Miglierini, Marcel B; Milová-Žiaková, Barbora; Farkas, Bence; Goneková, Zuzana; Vojtková, Hana; Matúš, Peter (The Science of the total environment, 2019)
Ferric oxyhydroxides are natural scavengers of antimony, thus, they contribute significantly to antimony immobilization in soils and sediments. Recent studies, however, usually omit microbial influence on geochemically stable antimony-ferric oxyhydroxide association. Therefore, we have evaluated fungal contribution to antimony mobility during static cultivation of common soil fungus Aspergillus niger in presence of ferric oxyhydroxides. Our results indicate distinguished effect of fungus on antimony distribution at two different antimony concentrations that were used for antimony pre-adsorbtion onto ferric oxyhydroxides prior to the inoculation. Approximately 36% of antimony was bioextracted by fungus from antimony bearing ferric oxyhydroxide after 14-day cultivation when the 8.9 mg·L-1 antimony concentration was used for pre-adsorption. However, no statistically significant change of antimony content in ferric oxyhydroxides was observed after cultivation when initial 48 mg·L-1 antimony concentration was used for pre-adsorption. As Mössbauer spectroscopy and XRD analysis indicated, nanosized akageneite, goethite, and lepidocrocite enhanced their crystallinity during cultivation, while hematite was identified only after the cultivation. Nevertheless, presence of ferric oxyhydroxides at both initial concentrations enabled transformation of antimony into volatile derivatives, and almost 9.5% of antimony was biovolatilized after cultivation. These results contribute significantly to environmental geochemistry of antimony-ferric oxyhydroxides association and highlight the importance of microbial activity in relation to ferric component of natural geochemical barriers.
Keywords: houby; biotransformace; Biotransformation; Soil Pollutants; adsorpce; látky znečišťující půdu; antimon; železité sloučeniny; Bioleaching; Aspergillus niger; Biovolatilization; Antimony; Ferric Compounds; Fungi; Adsorption